2015
DOI: 10.1371/journal.pone.0142338
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Lobar and Non-Lobar Intracerebral Hemorrhage in Patients with Vascular Disease

Abstract: IntroductionLobar and non-lobar non-traumatic intracerebral hemorrhage (ICH) are presumably caused by different types of small vessel diseases. The aim of this study was to assess risk factors for ICH according to location.MethodsIn two large prospective studies, SMART (n = 9088) and ESPRIT (n = 2625), including patients with manifest cardiovascular, cerebrovascular or peripheral artery disease or with vascular risk factors, we investigated potential risk factors for ICH during follow-up according to lobar or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Second, selection bias may play a role in that patients with a poor prognosis may have died before informed consent could be obtained. The sample size of patients with sICH was limited and we were therefore unable to distinguish lobar from nonlobar sICH, which have different risk profiles . Third, assessment of IS caused by SVD may have been prone to misclassification since, according to TOAST, support from imaging is not required.…”
Section: Discussionmentioning
confidence: 99%
“…Second, selection bias may play a role in that patients with a poor prognosis may have died before informed consent could be obtained. The sample size of patients with sICH was limited and we were therefore unable to distinguish lobar from nonlobar sICH, which have different risk profiles . Third, assessment of IS caused by SVD may have been prone to misclassification since, according to TOAST, support from imaging is not required.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that lobar localization, often seen in patients with cerebral amyloid angiopathy (CAA), is associated with recurrence. [8,19,31] The diagnosis CAA is not consistently registered, thus we were not able to investigate or adjust for it. As CAA is associated with elderly age, the missing information could potentially confound the results, and partially explain the high recurrence risk seen with elderly age after one year.…”
Section: Discussionmentioning
confidence: 99%
“…As one might expect, the underlying pathologies correlate with specific anatomical locations of the hemorrhage (Fazekas et al, 1999; Woo et al, 2002; Xiong et al, 2016). ICH is thought to be the result of SVD in up to 85% of hemorrhagic stroke patients, due to hypertensive arteriopathy-induced rupture of small arterioles in non-lobar regions, such as the basal ganglia, thalamus, cerebellum and brainstem (Kremer et al, 2015). However, a fairly large proportion of lobar ICHs result from rupture of small and medium-sized arteries in the elderly, due to accumulation of amyloid-beta in both cortical blood vessels and leptomeninges (Kremer et al, 2015).…”
Section: Age-related Vcidmentioning
confidence: 99%
“…ICH is thought to be the result of SVD in up to 85% of hemorrhagic stroke patients, due to hypertensive arteriopathy-induced rupture of small arterioles in non-lobar regions, such as the basal ganglia, thalamus, cerebellum and brainstem (Kremer et al, 2015). However, a fairly large proportion of lobar ICHs result from rupture of small and medium-sized arteries in the elderly, due to accumulation of amyloid-beta in both cortical blood vessels and leptomeninges (Kremer et al, 2015). Consistent with this view, CAA accounts for the majority of lobar ICH in the elderly (Greenberg, 1998; Hernandez-Guillamon et al, 2012; Knudsen et al, 2001), and is significantly associated with lobar and cerebellar ICH but not with deep ICH (Samarasekera et al, 2012; Yamada, 2015).…”
Section: Age-related Vcidmentioning
confidence: 99%